PENGEMBANGAN SEDIAAN SPRAY GEL DARI EKSTRAK ETANOL BATANG TUMBUHAN BAMBU-BAMBU (Polygonum pulchrum Blume) MENGGUNAKAN BASIS KOMBINASI GEL VISKOLAM® DAN Hydroxypropyl Methyl Cellulose (HPMC) - Wa Ode Sitti Zubaydah (MEDULA (JURNAL ILMIAH FAKULTAS KEDOKTERAN UNIVERSITAS HALU OLEO), 2022)
Background: Bamboo plants are one of the traditional medicinal plants that are often used by the community. The stem of Polygonum pulchrum Blume contains a triterpenoid steroid compound that acts as an active antioxidant. Objectives: This study aims to determine the optimal formula for spray gel preparation of Polygonum pulchrum Blume ethanol extract using Design Expert®. Methods: The stems of Polygonum pulchrum Blume were extracted by maceration using 96% ethanol to obtain a thick extract through . The extract obtained was formulated with spray gel preparations with variations in the concentration of viscolam® and HPMC F1(0,1%:0,1%), F2(0,4%:0,1%), F3(0,4%:0, 4%), and F4(0,1%:0,4%). The test was carried out by looking at the characteristics consisting of organoleptic test, pH test, viscosity test, spray pattern test, dry time test and homogeneity test, as well as looking at the stability of the preparation before and after the cycling test. Optimization of the spray gel formula using a factorial design of 23 with a viscolam® factor and HPMC using dry time response, viscosity, and spraying pattern. After obtaining the optimum formula, hedonic testing was carried out by looking at the parameters of color, aroma, texture, and overall appearance. Results and conclusions: The results showed that the optimum formula for the F2 formula was the concentration of viscolam® and HPMC 0.4%: 0.1%, as well as spray gel preparations that had been tested for stability and had met the stability test requirements based on the test parameters.